Polarization, Shifting Borders and Liquid Governance: Studies on Transformation and Development in the OSCE Region, edited Anja Mihr, and Chiara Pierobon. Springer Cham. XVII, 427 pp. https://doi.org/10.1007/978-3-031-44584-2 - Aleksanyan, Nane (Journal of Political Science: Bulletin of Yerevan University, 2024)
This book examines the dynamics of national and regional security in the age of Zeitenwende amid polarization and conflict management. Through a comparative analysis, the authors reveal the intricate problems of border dynamics and practice in cases of border disputes and conflicts in the member states of the OSCE. The authors offer their approaches on how to peacefully settle the disputed borders, which can be supported by the EU, the NATO and the OSCE. It can be of significant help in preventing security crises and conflicts. In this regard, a number of solutions that can affect the Russian-Ukraine war and the settlement of Russia-Ukraine relations are highlighted. From the author’s approach, it becomes clear that various European countries and international organizations should play an active role in the settlement of the Ukrainian crisis and the strengthening of European security.